2021
DOI: 10.1111/ibi.12941
|View full text |Cite
|
Sign up to set email alerts
|

Risk‐taking behaviour relates to timing of breeding in a sub‐Antarctic rainforest bird

Abstract: Within‐population variation in timing of breeding may be linked to a trade‐off between the risks and benefits of breeding earlier. This trade‐off may be mediated by individual risk‐taking behaviour, but this needs to be assessed in detail in wild populations. Here, we recorded timing of breeding and risk‐taking behaviour during three consecutive breeding seasons in a resident population of Thorn‐tailed Rayadito Aphrastura spinicauda located in Navarino Island (55°S), southern Chile. Navarino is a high‐latitude… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
3
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
5

Relationship

1
4

Authors

Journals

citations
Cited by 5 publications
(6 citation statements)
references
References 75 publications
0
3
0
Order By: Relevance
“…Rollers' risk-taking behaviour, both towards a novel object and a predator, was also influenced by laying date, with early breeders generally (but not always) performing better than late breeders. In birds, early breeders are often older or more experienced individuals, selecting higher quality breeding areas, having higher reproductive success, and being more risk prone (Verhulst & Nilsson 2008;Brommer et al 2014;Winkler 2016;Poblete et al 2021). Our data, from six consecutive breeding seasons, showed that early breeding rollers laid more eggs and had higher productivity (number of fledging chicks) than late breeders.…”
Section: Other Factors Influencing Roller's Risk-taking Behaviourmentioning
confidence: 69%
See 1 more Smart Citation
“…Rollers' risk-taking behaviour, both towards a novel object and a predator, was also influenced by laying date, with early breeders generally (but not always) performing better than late breeders. In birds, early breeders are often older or more experienced individuals, selecting higher quality breeding areas, having higher reproductive success, and being more risk prone (Verhulst & Nilsson 2008;Brommer et al 2014;Winkler 2016;Poblete et al 2021). Our data, from six consecutive breeding seasons, showed that early breeding rollers laid more eggs and had higher productivity (number of fledging chicks) than late breeders.…”
Section: Other Factors Influencing Roller's Risk-taking Behaviourmentioning
confidence: 69%
“…Year was not included in the model was there was no difference in roller's response between years (w74 = 597, P = 0.306). Laying date was used to control for individual traits/experience, under the assumption that early breeders are older, more experienced individuals and more risk prone (Verhulst & Nilsson 2008;Brommer et al 2014;Winkler 2016;Poblete et al 2021). A log-link was used as data had a right-skewed distribution.…”
Section: Influence Of Social Context In Risk-taking Behaviour Towards...mentioning
confidence: 99%
“…3 ). Similar methods have been used to infer aspects of avian locomotory behavior such as exploration (McCowan et al 2015 ; Huang et al 2012 ), risk-taking (Pobleté et al 2021 ), and boldness (McCowan et al 2015 ). We performed each activity assay between 09:00 and 15:00 in a soundproof, indoor aviary (3L × 3W × 2.5H m).…”
Section: Methods—procedures Common To All Studiesmentioning
confidence: 99%
“…To evaluate exploratory behavior, we conducted novel environmental tests shortly after capturing the birds, following the protocol described by Verbeek et al (1996). To this end, we used a field-portable aviary (270 cm long × 150 cm wide × 150 cm high) made of removable poles and semitransparent black cloth (see Poblete et al, 2018Poblete et al, , 2021Botero-delgadillo, Quirici, Poblete, Poulin, et al, 2020 for aviary details). The aviary had 14 possible perching locations, including perches and walls.…”
Section: Exploratory Behaviormentioning
confidence: 99%
“…About 1 min before starting the trial, we removed this cloth, and the door of the acclimatization cage was opened for each subject who was free to explore. We used a digital camera (Sony DCR-68) for recording the behavior of each bird for 10 min (Botero-delgadillo et al, 2019;Poblete et al, 2018Poblete et al, , 2021.…”
Section: Exploratory Behaviormentioning
confidence: 99%